The Influence of Employee Feedback and Incentives on Employee Work Motivation at CV BWS Trans Lintang, Palembang City - M.H, Nisyah Audya; Kurniawan, Mohammad; Lazuarni, Shafiera (Universitas Pamulang, 2025)
Work motivation is a key factor influencing employee productivity and performance within a company. This study aims to analyze the effect of employee feedback and incentives on increasing work motivation among employees at the shipping service company CV BWS Trans Lintang. A quantitative research method was employed, using questionnaires distributed to all employees of the company. The collected data were analyzed using multiple linear regression with the help of SPSS version 26. The results show that employee feedback has a positive and significant effect on work motivation, as clear and structured feedback enhances employees’ understanding of company expectations and encourages performance improvement. In addition, incentives also have a positive impact on work motivation-both financial and non-financial-as they provide recognition and foster employee loyalty and commitment to the company. Simultaneously, employee feedback and incentives significantly contribute to improving work motivation. This study offers practical implications for the management of CV BWS Trans Lintang by highlighting the importance of strengthening performance evaluation strategies and incentive policies to create a more productive and conducive work environment. Theoretically, the study enriches the literature on human resource management by providing empirical evidence on the significance of feedback mechanisms and incentive systems in enhancing work motivation, particularly in the context of shipping service companies facing dynamic and service-oriented operational challenges.